Fibril-mediated adherence of Actinomyces viscosus to saliva-treated hydroxyapatite. - Wheeler, T T (1980)
Fibril-mediated adherence of Actinomyces viscosus strain T14V cells to saliva-treated hydroxyapatite was studied. Fibrils were purified by ammonium sulfate precipitation and differential centrifugation from the crude supernatant of whole cells that were sheared by one passage through a French pressure cell. Purified fibrils and crude supernatant inhibited strain T14V adherence to saliva-treated hydroxyapatite to similar extents. However, anti-strain T14V serum and antifibril specific antibody completely abolished strain T14V adherence. The blocking immunoglobulin could be adsorbed from anti-T14V serum by strain T14V whole cells, by purified fibrils, and, to a lesser extent, by cell walls. It was concluded that fibrils mediate adherence of strain T14V cells to saliva-treated hydroxyapatite. In addition, fibril preparations were shown to contain more than 95% protein and to be antigenically homogeneous by immunodiffusion and Laurell rocket immunoelectrophoresis. Purified fibril preparations showed serological identity with the virulence-associated 1 antigen of Lancefield-extracted T14V cells, whereas crude supernatants contained both virulence-associated 1 and virulence-associated 2 antigens, as shown by rocket immunoelectrophoresis.